Energy substrate supplementation increases ATP levels and is protective to PD neurons - Andrey Y. Vinokurov; Marina Y. Pogonyalova; Larisa Andreeva; Andrey Y. Abramov; Plamena R. Angelova (Elsevier, 2024)
Alteration of mitochondrial metabolism by various mutations or toxins leads to various neurological conditions. Age-related changes in energy metabolism could also play the role of a trigger for neurodegenerative disorders. Nonetheless, it is not clear if restoration of ATP production or supplementation of brain cells with substrates for energy production could be neuroprotective. Using primary neurons and astrocytes, and neurons with familial forms of neurodegenerative disorders we studied whether various substrates of energy metabolism could improve mitochondrial metabolism and stimulate ATP production, and whether increased ATP levels could protect cells against glutamate excitotoxicity and neurodegeneration. We found that supplementation of neurons with several substrates, or combination thereof, for the TCA cycle and cellular respiration, and oxidative phosphorylation resulted in an increase in mitochondrial NADH level and in mitochondrial membrane potential and led to an increased level of ATP in neurons and astrocytes. Subsequently, these cells were protected against energy deprivation during ischemia or glutamate excitotoxicity. Provision of substrates for energy metabolism to cells with familial forms of Parkinson's disease also prevented triggering of cell death. Thus, restoration of energy metabolism and increase of ATP production can play neuroprotective role in neurodegeneration. A combination of a succinate salt of choline and nicotinamide provided the best results.